Modelling of debonded reinforcement in ABC connections designed for seismic zones. (1st November 2019) - Mantawy, Islam M.; Sanders, David H.; Eberhard, Marc O.; Stanton, John F.
Highlights: Bridge specimen with pretensioned, rocking columns was tested dynamically. Methodology for modelling debonded longitudinal reinforcement in ABC for seismic zone. Low cycle fatigue material is used to capture the fracture of longitudinal reinforcement. Fracture of longitudinal reinforcing steel due to accumulation of strain cycles. Parametric Study enhanced the bridge behavior by iterating on model parameters. Abstract: There are multiple design and detailing approaches for accelerated bridge construction (ABC) in seismically active zones. One of the most common methods is the use of precast components. When using precast components, a technique that can improve seismic behavior is debonding of the longitudinal reinforcement and/or prestressing strands; this can achieve the following objectives: (1) reducing concrete stress concentration, (2) promote rocking behavior, and (3) controlling/delaying the fracture of longitudinal bars. One example of debonding column reinforcement for ABC systems was a pretensioned rocking system that was tested using the shake table facility at the University of Nevada, Reno in 2014. A new numerical modelling strategy was developed to model the debonded reinforcement using external elements explicitly modelled and connected to the column element using rigid links at their proper arms. A numerical model was developed using Opensees for the selected bridge specimen by implementing the suggested strategy to capture the measured response in global and local domains. By incorporating a fatigue material with the reinforcement steel model, this strategy showed excellent agreement with the measured response. Then, the calibrated numerical model was used to explore methods to improve the performance of the system by delaying reinforcing steel fracture. The parametric studies show that increasing the bar sizes and the locally debonded length of the reinforcement were both effective strategies to reduce and delay bar fracture.